Pests of Roses in Florida - Gary W. Knox; Russell F. Mizell, III (EDIS)
ENH-1108, a 7-page illustrated fact sheet by Gary W. Knox and Russell F. Mizell, III, provides basic information for homeowners on minimizing rose pests through selection and care, describes major pests of roses, as well as other diseases, insect, mites, arthropods, and animals that are pests of roses. Includes references. Published by the UF Department of Environmental Horticulture, September 2008.